(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Fire detection is a critical task for ensuring the safety of both people and property. Deploying the system in buildings, factories, and public spaces to ensure early fire detection and quick response, minimizing the risk of casualties and property damage